Heterogeneity in real wage cyclicality - Pedro Silva Martins (Institute for the Study of Labor (IZA), 2007)
This paper presents evidence that real wage cyclicality can be a particularly heterogeneous parameter, depending on different worker characteristics and also on the specific stage of the business cycle. Using matched employer-employee panel data for Portugal covering the period 1986-2004, real wages are shown to be considerably more procyclical during recessions than during expansions, resulting in relatively moderate overall levels of cyclicality (about -0.6). However, most of the procyclicality during downturns is shown to be driven by the younger employees, as older workers appear to be insulated from the business cycle. Moreover, movers between firms typically display higher cyclicality than workers that stay in the same firm, regardless of whether the latter move or not between job levels. Most results also hold when considering basic wages instead of total wages, except that the procyclicality of movers during downturns is substantially higher.
Keywords: 330; Reallohn; Konjunktur; Schätzung; Portugal